Pengaruh Big Five Personality Dan Komitmen Organisasional Afektif Terhadap Organizational Citizenship Behavior Tenaga Administrasi Tetap: Sebuah Penelitian Kasus Pada Universitas Kristen Maranatha Bandung - Denalia Tri Arini Suherli; Sunjoyo . (Jurnal Manajemen Maranatha, 2011)
This research is a development of the previous research which had done by Purba and Seniati (2004). The purpose of this study is to test whether big five personality and affective organizational commitment positively affect on organizational citizenship behavior (OCB). The respondents in this research are the administrative staffs at Maranatha Christian University (MCU), Bandung. One hundred seventeen of 199 data were useable. There were two hypotheses that formulated in this research and all hypotheses supported by the empirical data. Simple regression analysis was used to test two hypotheses. The result of this research shows that the big five personality and affective organizational commitment positively influence on organizational citizenship behavior at Maranatha Christian University. The implications of these findings were discused for the future researches were advised.Keywords: big five personality, affective organizational commitment, organizational citizenship behavior (OCB)